1997
DOI: 10.2337/diab.46.6.1054
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Decreases the Occurrence of Malformations in the Offspring of Diabetic Rats

Abstract: An association between excess oxygen radical activity and disturbed embryogenesis in diabetic pregnancy has been suggested. In the present study, the protective capacity of vitamin E with different treatment regimens was investigated in early and late pregnancy of streptozotocin-induced diabetic rats. Daily gavaging of 0.2 g/kg or 0.8 g/kg of vitamin E exerted moderate protective effects. In contrast, treatment with a diet enriched with 2% (wt/wt) of vitamin E, yielding an approximate daily dosage of 2 g/kg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…Consequently, supplementation of anti-oxidants is able to lower the incidence of defects in diabetic pregnancies [Reece and Wu, 1997; Siman and Eriksson, 1997; Wiznitzer et al, 1999a; Cederberg et al, 2001; Sugimura et al, 2009]. It has been suggested that in this context, folic acid also acts as an anti-oxidant, as it is able to reduce neural tube defect rates in pregnancies affected by hyperglycemia [Gareskog et al, 2006; Oyama et al, 2009].…”
Section: Maternal Diabetes and Neural Tube Defects In Animal Modelsmentioning
confidence: 99%
“…Consequently, supplementation of anti-oxidants is able to lower the incidence of defects in diabetic pregnancies [Reece and Wu, 1997; Siman and Eriksson, 1997; Wiznitzer et al, 1999a; Cederberg et al, 2001; Sugimura et al, 2009]. It has been suggested that in this context, folic acid also acts as an anti-oxidant, as it is able to reduce neural tube defect rates in pregnancies affected by hyperglycemia [Gareskog et al, 2006; Oyama et al, 2009].…”
Section: Maternal Diabetes and Neural Tube Defects In Animal Modelsmentioning
confidence: 99%
“…There is ample experimental support that oxidative stress contributes to malformations in animal models exposed to a high glucose milieu [37, 5155]. In addition to increased superoxide production from increased oxidative metabolism, the pathways responsible for oxidative stress are complex; they include decreased expression of γ -glutamyl-cysteine synthetase, which would decrease production of the antioxidant, reduced glutathione (GSH) [123, 124], and increased activity of the hexosamine flux pathway and diacylglycerol/protein kinase C signaling [40, 125].…”
Section: Mechanisms By Which Maternal Diabetes Disrupts Pax3 Gene Expmentioning
confidence: 99%
“…In general, these models result in malformation of craniofacial structures and the neural tubes and growth retardation. There are several biochemical disturbances that have been proposed to play a role in the defective development, such as increased protein kinase C activity [3840], decreased arachidonic acid uptake [41, 42], defective prostaglandin synthesis [43, 44], PPAR signaling [4548], random DNA mutations [49, 50], and oxidative stress [37, 5155]. However, none of these studies revealed how these biochemical disturbances could disturb morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…That homozygous mutant Pax3 mouse embryos develop NTD and COTD with 100% penetrance (13,14) supports the notion that inhibition of Pax3 below a critical threshold is sufficient to cause NTD or COTD in embryos of diabetic mothers. Several studies have indicated that oxidative stress produced in the embryo in response to increased glucose metabolism is responsible for diabetic pregnancy–induced malformations (1520). We have shown that oxidative stress inhibits expression of Pax3 (21,22).…”
Section: Introductionmentioning
confidence: 99%